Perlindungan Hukum Terhadap Investor Sebagai Konsumen dalam Investasi Online - Kadek Desy Pramita; Kadek Diva Hendrayana (Universitas Pendidikan Ganesha, 2021)
Today’s technological development have led to the emergence of online investing. The exixtence of online investing makes it easy for people to invest their wealth, simply by accessing sites that offer investment. However online investing has a negative impact on consumers. Therefore, this study aims to determine legal protection efforts against investors as consumers in online investment. The research method used in this research is doctrinal research method, with descriptive analytical research specifications and data analysis using qualitative methods. Then the result show that the legal protection for online investors can be carried out by the OJK in a preventive and repressive way.